THE IMPACT OF MULTIGRADE TEACHING APPROACH IN TEACHING OF BASIC SCIENCE - Funtua, Ismail Ado (PEOPLE: International Journal of Social Sciences, 2015)
A major challenge in the teaching of science at Basic Education (BE) level in Nigeria has been the inadequate number of qualified teachers, coupled with insufficient materials and the overcrowded classroom conditions in cities (Miller 1989). In remote environments, the situation is different, where there are few children in two or more grades with one or two teachers, and usually among them one is an Arabic teacher. This poses a serious challenge in the learning / teaching condition of these kinds of schools. The use of multigrade teaching approach in this situation seems to be a viable option. In this research, six schools were selected from three geo-political zones in Katsina state, Northern Nigeria. In each zone one school is used as experimental group and another one as control group. Pupils (subjects) were assessed using an achievement test constructed by the researcher based on the concepts taught. The results indicated a significant relationship between the use of multigrade teaching and pupils’ academic achievement. While a gender comparison of subjects taught using the multigrade teaching approach and their counterparts taught using the monograde approach revealed a significant difference in their academic achievement. The paper concluded with some recommendations to education stakeholders especially the Local Education Authorities (LEAs), State Universal Basic Education Boards (SUBEBs) and the International development Partners (IDPs) for more support in the retraining of teachers on multigrade teaching approach not only in the teaching of Basic science, but all subjects.